Fractal analysis of 2D and 3D mesocracks in recycled aggregate concrete using X-ray computed tomography images. (1st July 2021) - Shang, Xiaoyu; Yang, Jingwei; Wang, Simiao; Zhang, Mingzhong
Abstract: Recycled aggregates can introduce initial defects and damage to prepared concrete. Internal mesocrack formation is a fatal factor influencing the durable and mechanical properties of recycled aggregate concrete. In this study, the internal mesocracks of recycled aggregate concrete (RAC) under uniaxial compressive loading were virtually and quantitatively investigated by using the X-ray computed tomography (CT) technique. Statistical analysis was conducted on the number, length, width, tortuosity and density of mesocracks in RAC under critically damaged conditions. Then, these mesocracks were numerically extracted and restored to 2D images and 3D structures based on the digital matrix method for fractal geometry analysis. Fractal characteristics and multifractal spectra were used to analyse the mesocrack characteristics of RAC with different recycled coarse aggregate (RCA) replacement rates. The results show that the total number, width, tortuosity and density of mesocracks decrease with increasing RCA replacement rate. The mesocracks inside concrete have self-similarity characteristics, and the corresponding region is a multifractal body. It is feasible to quantitatively characterize mesocrack propagation in the fractal dimension. A clear correlation exists between the fractal dimension and RCA replacement rate: the higher the RCA replacement rate is, the lower the fractal dimension, and the less tortuous the mesocracks. The fractal dimension of mesocracks ranged from 1.19 to 1.32 and 2.18 to 2.39 for 2D images and 3D structures, respectively. Compared with ordinary concrete, the introduction of recycled aggregates leads to a maximum 10% reduction in fractal dimension. The multifractal spectrum effectively reflects the characteristics of mesocracks at different levels from the local to the global level. Although statistical results indicate that the mesocrack characteristics from 3D structures supply more accurate information than the description from 2D images, mesocracks obtained from 3D structures have fractal characteristics similar to those of 2D images. Highlights: X-ray CT was used to investigate the internal mesocracks of recycled aggregate concrete. Mesocrack characteristics were comparably analysed by statistical methods and factual geometry theory. The fractal dimension and multifractal spectrum are effective means to quantify the mesocrack distribution. Mesocrack growth was discussed at different scales: 2D images and 3D structures.